The usage of marginal aggregate as subbase layer - Adelia Dwidarma Nataadmadja; Eduardi Prahara; Andreas Bennardi (SINERGI, 2024)
Aggregate holds the main role in determining the quality of pavement layers. Unfortunately, the locally available aggregates sometimes did not pass one or more requirements stated in the standard, making these aggregates technically unable to be used. These aggregates are called marginal or substandard aggregates. However, previous research projects have shown the potential of utilizing marginal aggregates as pavement layers. This research aims to analyst the techniques for utilizing marginal aggregates as pavement layers, specifically as subbases. Two techniques were evaluated herein, namely by varying the aggregate gradation and by adding cement and lime as stabilizers, and the specimens were assessed by the California Bearing Ratio (CBR) test. The research results found that varying the percentage of coarse and fine aggregates in the specimens improved the CBR value. The specimen obtained the highest CBR value with 70% coarse aggregate and 30% fine aggregate. Moreover, it was found that adding cement and lime as stabilizers at the right percentage was also able to improve the CBR value of the specimens and mixing the stabilizers beyond a certain percentage decreases the CBR value. The amount of cement and lime needed depended on the aggregate gradation used.